2023
DOI: 10.3201/eid2910.230084
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Bacteremia from Gastrointestinal Perforation after Natto Ingestion, Japan

Takehiro Hashimoto,
Takaaki Yahiro,
Sakirul Khan
et al.

Abstract: We report a case of Bacillus subtilis variant natto bacteremia from a gastrointestinal perforation in a patient who ingested natto. Genotypic methods showed the bacteria in a blood sample and the ingested natto were the same strains. Older or immunocompromised patients could be at risk for bacteremia from ingesting natto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…natto, such as bloodstream infections and meningitis in natto consumers. 1 , 2 , 3 , 6 To our knowledge, this case is the first report of community‐acquired pneumonia via this pathogen. The mechanism of pneumonia is unclear.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…natto, such as bloodstream infections and meningitis in natto consumers. 1 , 2 , 3 , 6 To our knowledge, this case is the first report of community‐acquired pneumonia via this pathogen. The mechanism of pneumonia is unclear.…”
Section: Discussionmentioning
confidence: 74%
“…natto , particularly in cases of gastrointestinal perforation or immunocompromised individuals. 1 , 2 , 3 On the contrary, there are no reports of community‐acquired pneumonia in an immunocompetent host. We report a case of pneumonia and bacteremia caused by B. subtilis subsp .…”
Section: Introductionmentioning
confidence: 99%
“…Only four cases of bacteremia caused by B. subtilis var. natto have been reported previously, all of which were associated with immunodeficiency or gastrointestinal lesions [1] , [2] , [3] , [4] . Here, we report a case of persistent bacteremia caused by B. subtilis var.…”
Section: Introductionmentioning
confidence: 62%
“…natto is a less toxic bacterium, it is thought that reduced immunity puts patients at risk of developing the disease. Tanaka et al [2] and Hashimoto et al [3] reported cases of B. subtilis var. natto bacteremia in patients with gastrointestinal perforation, whereas Tokano et al reported a case of B. subtilis var.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic usage of Shouchella clausii (Bacillus clausii) (Erbas et al, 2023) and of Bacillus licheniformis (Zou et al, 2024) leads to bacteraemia in an immunocompromised patient. Bacteraemia related to Bacillus subtilis (Hashimoto et al, 2023;Kato et al, 2022;Ochi et al, 2023;Tokano et al, 2023) was diagnosed in immunocompromised patients.…”
Section: Bacillus Spp and Related Speciesmentioning
confidence: 99%